Biomining Sesuvium portulacastrum for halotolerant PGPR and endophytes for promotion of salt tolerance in Vigna mungo L. - John, Joseph Ezra; Maheswari, Muthunalliappan; Kalaiselvi, Thangavel; Prasanthrajan, Mohan; Poornachandhra, Chidamparam; Rakesh, Srirangarayan Subramanian; Gopalakrishnan, Boopathi; Davamani, Veeraswamy; Kokiladevi, Eswaran; Ranjith, Sellappan (Frontiers in Microbiology, 2023)
Halophytic plants can tolerate a high level of salinity through several morphological and physiological adaptations along with the presence of salt tolerant rhizo-microbiome. These microbes release phytohormones which aid in alleviating salinity stress and improve nutrient availability. The isolation and identification of such halophilic PGPRs can be useful in developing bio-inoculants for improving the salt tolerance and productivity of non-halophytic plants under saline conditions. In this study, salt-tolerant bacteria with multiple plant growth promoting characteristics were isolated from the rhizosphere of a predominant halophyte, Sesuvium portulacastrum grown in the coastal and paper mill effluent irrigated soils. Among the isolates, nine halotolerant rhizobacterial strains that were able to grow profusely at a salinity level of 5% NaCl were screened. These isolates were found to have multiple plant growth promoting (PGP) traits, especially 1-aminocyclopropane-1-carboxylic acid deaminase activity (0.32 - 1.18 µM of α-ketobutyrate released mg-1 of protein h-1) and indole acetic acid (9.4 - 22.8 µg mL-1). The halotolerant PGPR inoculation had the potential to improve salt tolerance in Vigna mungo L. which was reflected in significantly (P>0.05) higher germination percentage (89%) compared to un-inoculated seeds (65%) under 2% NaCl. Similarly, shoot length (8.9 - 14.6 cm) and vigour index (792-1785) were also higher in inoculated seeds. The strains compatible with each other were used for the preparation of two bioformulations and these microbial consortia were tested for their efficacy in salt stress alleviation of Vigna mungo L. under pot study. The inoculation improved the photosynthetic rate (12%), chlorophyll content (22%), shoot length (5.7%) and grain yield (33%) in Vigna mungo L. The enzymatic activity of catalase and superoxide dismutase were found to be lower (7.0 and 1.5%, respectively) in inoculated plants. These results revealed that halotolerant PGPR isolated from S. portulacastrum can be a cost-effective and ecologically sustainable method to improve crop productivity under high saline conditions.